Why Obergefell Should Not Impact Amerian Indian Tribal Marriage Laws - Steven J. Alagna (Washington University Law Review, 2016)
This Note explores what Obergefell means for members of American Indian nations, and it argues that Obergefell should not constrain tribal governments. Part I briefly recounts Obergefell, including the Court’s reasoning and language that might be pertinent for tribal sovereigns. Part II briefly surveys the status of tribal same-sex marriage laws to reveal the pluralism amongst the Native nations that have definitively decided the issue. Part III discusses how these tribes’ decisions are rooted in tradition and self-determination, two indeterminate concepts that contribute to Native pluralism on the issue. Part IV explores the interplay of tribal, state, and federal law, unpacking tribal nations’ special status as “domestic dependent nations,” and what this means for tribal marriage laws that accord or contrast with the laws of other jurisdictions. Finally, Part V argues that Obergefell should have only a limited, indirect impact on tribal marriage laws, and discusses why the “should” in this sentence and this Note’s title is both predictive and normative.
Keywords: obergefell; american indian; marraige; tribe